Analysis of the Community Satisfaction Index at the Talang Perapat Village Office, Seluma District, Bengkulu Province - Sukman Sukman; Sulistri Afriani; Sri Handayani (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
The sample in this study consisted of 80 people from the Talang Perapat Village, Seluma District, who received services from Talang Perapat Village, Seluma District. Data collection uses a questionnaire. The data analysis technique used is to measure the value of the Community Satisfaction Index (IKM) based on the Minister of State Apparatus Empowerment and Bureaucratic Reform Regulation Number 14 of 2017. The Community Satisfaction Index (IKM) for the quality of service at the Talang Perapat Village Office, Seluma District, Bengkulu Province obtained an average value of 3.28, which is considered good. Next, the service unit IKM is multiplied by 25 so that the IKM at the Talang Perapat Village Office, Seluma District, Bengkulu Province is 82.03 with service quality B with good criteria because it is in the value interval of 76.61 – 88.30. The cost/tariff element received the highest assessment with an average value of 3.61 with very good assessment criteria. This illustrates that the community considers that the Talang Perapat Village Office, Seluma District, Bengkulu Province provides services free of charge.